Hubungan Terpaan Konten Thread affiliate dengan Perilaku Impulsive buying - Febilla Parindra; Ratih Pandu Mustikasari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Affiliate thread content on social media has become an increasingly common marketing strategy, particularly in reaching active digital users. On platform X, affiliate threads are still frequently encountered by users and are typically presented in the form of persuasive narratives combined with attractive product visuals. This format has the potential to influence users emotionally and trigger spontaneous purchasing behavior. This study aims to examine the relationship between the intensity of exposure to affiliate threads and users’ impulsive buying behavior, while also exploring how consumer decision-making processes can be explained using the Elaboration Likelihood Model (ELM). This research applies a quantitative approach using a survey method involving 100 respondents who are active users of platform X and have previously read or made purchases through affiliate threads. The exposure variable was analyzed through three main indicators: frequency, duration, and attention. Meanwhile, the impulsive buying variable was examined through four components: spontaneity, compulsive urge, emotional involvement, and disregard for consequences. Data analysis was conducted using the Spearman Rank correlation test. The findings show a very strong and significant relationship between exposure to affiliate thread content and impulsive buying behavior. The peripheral route was found to be the dominant path in explaining purchase decisions, evident in the strong influence of product visuals, narrative appeal, and ease of access to purchase links. However, a small number of respondents also showed signs of central route processing, particularly when evaluating product usefulness and financial impact. These results indicate that both routes in ELM remain relevant in understanding impulsive consumer behavior in the digital age.